2020
DOI: 10.1039/d0ew00027b
|View full text |Cite
|
Sign up to set email alerts
|

Biochar-augmented biofilters to improve pollutant removal from stormwater – can they improve receiving water quality?

Abstract: Stormwater biofilters are being implemented widely in urban environments to provide green space, alleviate flooding, and improve stormwater quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
28
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 120 publications
(180 reference statements)
0
28
1
Order By: Relevance
“…It has been widely reported that biochar can be used directly as a renewable energy source [2], as a soil amendment to improve fertility [3] and control soil greenhouse gas emission [4,5], and as a filter media for wastewater treatment [6]. The process of making biochar produces less air pollution than the open burning of agricultural residues in fields, which can emit noxious gases (CO, SOx, NOx) and smoke particles carrying carcinogen substances [7].…”
Section: Introductionmentioning
confidence: 99%
“…It has been widely reported that biochar can be used directly as a renewable energy source [2], as a soil amendment to improve fertility [3] and control soil greenhouse gas emission [4,5], and as a filter media for wastewater treatment [6]. The process of making biochar produces less air pollution than the open burning of agricultural residues in fields, which can emit noxious gases (CO, SOx, NOx) and smoke particles carrying carcinogen substances [7].…”
Section: Introductionmentioning
confidence: 99%
“…As illustrated in Figure 1a, these vertically oriented systems filter water through planted soil or sand‐based media and are easily integrated into the urban landscape over a range of scales (Grant et al., 2013; Roy‐Poirier et al., 2010; Wong, 2006). Their possible features include: (1) a ponding zone that retains water prior to infiltration; (2) biological components including upright vegetation and naturally colonizing soil invertebrates and microorganisms; (3) engineered filter media (sand, sandy loam, or loamy sand with or without media amendments [e.g., biochar; Boehm et al., 2020; Mohanty & Boehm, 2014]); (4) a coarse sand transition layer; (5) a drainage layer consisting of coarse sand or fine gravel which can be lined or unlined and with or without an underdrain; (6) an overflow structure that releases excess storm water; and (7) a raised outlet to facilitate the formation of a permanently wet “submerged zone” (Clar et al., 2004; A. P. Davis et al, 2009; H. Kim et al., 2003; Payne et al., 2015; Rippy, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…(3) engineered filter media (sand, sandy loam, or loamy sand with or without media amendments [e.g., biochar; Boehm et al, 2020;Mohanty & Boehm, 2014]); (4) a coarse sand transition layer; (5) a drainage layer consisting of coarse sand or fine gravel which can be lined or unlined and with or without an underdrain; (6) an overflow structure that releases excess storm water; and (7) a raised outlet to facilitate the formation of a permanently wet "submerged zone" (Clar et al, 2004;A. P. Davis et al, 2009; H. Kim et al, 2003;Payne et al, 2015;Rippy, 2015).…”
mentioning
confidence: 99%
“…Researchers have studied the use of engineered geomedia, such as manganese oxide-coated sands ( Charbonnet et al., 2020 ; Grebel et al., 2016 ), woodchips ( Ashoori et al., 2019 ), functionalized clays ( Ray et al., 2019 ) and biochar ( Ashoori et al., 2019 ; Boehm et al., 2020 ; Ulrich et al., 2015 ) as a passive means of stormwater treatment. However, such treatment systems are often limited by the low hydraulic conductivities of geomedia or underlying soils and sediments ( Barnes et al., 2014 ; Minnesota Stormwater Steering Committee 2005 ; Ray et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%